The effects of different forms of caffeine supplement on 5-km running performance - Whalley, P. J.; Dearing, C. G.; Paton, C. D. (International Journal of Sports Physiology and Performance, 2020)
Purpose: Caffeine is frequently used by athletes as an ergogenic aid. Various alternate forms of caffeine administration are available, which may produce different effects. This investigation compares the effects of different forms of caffeine supplementation on 5-km running performance, and the relationship between athlete ability and degree of enhancement attained. Methods: Fourteen amateur runners completed a series of self-paced outdoor time trials following unknown ingestion of a placebo (P) or one of 3 alternate forms of caffeine supplement. Trials were randomized in a crossover design with caffeine (approximately 3-4.5 mg/kg) administered 15 minutes before each trial via chewing gum (CG), dissolvable mouth strips (CS), or tablet (CT). Results: Compared with P, all caffeine supplements led to worthwhile enhancements in running performance with a mean (±95% confidence limit) overall effect across all supplements of 1.4%±0.9%. Individual caffeine treatment effects (CG=0.9%±1.4%, CS=1.2%±1.0%, and CT=2.0%±1.1%) were not significantly different (P>.05) from each other; however, CT trials produced the largest gain and was significantly different (P=.02) compared with P. There was no significant difference in heart rate or rate of perceived exertion across the performance trials. The magnitude of caffeine enhancement was also strongly correlated (r=.87) with no-treatment performance time. Conclusions: The findings showed that irrespective of delivery form, moderate dose of caffeine supplementation produces worthwhile gains in 5-km running performance compared with a P. Furthermore, the magnitude of caffeine enhancement is highly individualized, but it appears related to athlete performance ability.